Cytosolic Ca2+ signals enhance the vacuolar ion conductivity of bulging arabidopsis root hair cells - Wang, Yi; Krebs, Melanie; Schumacher, Karin (Molecular plant, 2015)
Plant cell expansion depends on the uptake of solutes across the plasma membrane and their storage within the vacuole. In contrast to the well-studied plasma membrane, little is known about the regulation of ion transport at the vacuolar membrane. We therefore established an experimental approach to study vacuolar ion transport in intact Arabidopsis root cells, with multi-barreled microelectrodes. The subcellular position of electrodes was detected by imaging current-injected fluorescent dyes. Comparison of measurements with electrodes in the cytosol and vacuole revealed an average vacuolar membrane potential of −31 mV. Voltage clamp recordings of single vacuoles resolved the activity of voltage-independent and slowly deactivating channels. In bulging root hairs that express the Ca2+ sensor R-GECO1, rapid elevation of the cytosolic Ca2+ concentration was observed, after impalement with microelectrodes, or injection of the Ca2+ chelator BAPTA. Elevation of the cytosolic Ca2+ level stimulated the activity of voltage-independent channels in the vacuolar membrane. Likewise, the vacuolar ion conductance was enhanced during a sudden increase of the cytosolic Ca2+ level in cells injected with fluorescent Ca2+ indicator FURA-2. These data thus show that cytosolic Ca2+ signals can rapidly activate vacuolar ion channels, which may prevent rupture of the vacuolar membrane, when facing mechanical forces.